Avaliação das alterações retinianas em olhos de coelho após injeções intravítrea de sunitinibe, nanopartículas lipídicas sólidas e nanocápsulas - Freitas, Luiz Guilherme Azevedo de (2015)
To evaluate the safety of single intravitreal injection of 0,1ml of sunitinib (one group with 1mg/ml and the other group with 10mg/ml), 0,1ml of a solution containing solid lipid nanoparticles and 0,1ml of a solution containing nanocapsules analyzing the possible toxic effects by the electrophysiology and histology in the albino rabbits retina. An experimental controlled study was performed with 20 eyes of albino rabbits. It were performed intravitreal injections of 0,1ml (1mg/ml) of sunitinib in 5 eyes, 0,1ml (10mg/ml) of sunitinib in 5 eyes, 0,1ml of nanocapsules solution in 5 eyes and 0,1ml of a solution containing solid lipid nanoparticles in 5 eyes. Contralateral eye did not receive any treatment and was used as control. Changes in electroretinography were not observed in groups of sunitinib (1mg/ml and 10mg/ml) and in the group of solid lipid nanoparticles. However, in the group of the nanocapsules significant changes were found. They were in the morphology and at the electroretinogram. At histological study only the group of nanocapsules degenerative changes were detected. Changes were severe edema and formation of cytoplasmic vacuoles, suggesting retinal toxicity.